1989
DOI: 10.3109/17453678909149596
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography and radiography of the hip in infants

Abstract: Both hip joints in 156 children, aged 2 months to 2 years, were examined by ultrasonography (ultrasound) and radiography. Pathologic findings were based on an increased acetabular index, bony defects of the lateral acetabular rim, and lateral and/or proximal displacement of the proximal femur. Each hip was classified as normal, dysplasia, subluxation, or dislocation. The same diagnosis was reached by ultrasound and radiography in 303 of the 312 hips. The accordance was good in normal joints, in subluxation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 18 publications
3
38
1
Order By: Relevance
“…Thus, it is essential to establish the limits of normal variation of LHD in the various age groups. The present results showed somewhat smaller values for the upper normal limit of LHD in the two youngest age groups than did our previous study (Terjesen et al 1991). Based on both these studies, the following upper normal limits are suggested: 4 mm at age 2-3 years, 5 mm at 4-7 years, 6 m m at 8-1 1 years, and 7 mm in adolescents above I 1 years of age.…”
Section: Discussioncontrasting
confidence: 50%
See 4 more Smart Citations
“…Thus, it is essential to establish the limits of normal variation of LHD in the various age groups. The present results showed somewhat smaller values for the upper normal limit of LHD in the two youngest age groups than did our previous study (Terjesen et al 1991). Based on both these studies, the following upper normal limits are suggested: 4 mm at age 2-3 years, 5 mm at 4-7 years, 6 m m at 8-1 1 years, and 7 mm in adolescents above I 1 years of age.…”
Section: Discussioncontrasting
confidence: 50%
“…Although ultrasound (like radiography) entails potential measurement errors due to patient positioning, transducer position, and identification of anatomic landmarks on images, the moderate interobserver variation of f 1 mm (Terjesen et al 1991) confirms our experience that the technique is appropriate in clinical practice.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations